Real options approach to valuation of fuel cell companies. - Shriram Subramanian. (2008)
This paper develops a growth option model for the valuation of a part of the business of Ballard Power Systems, a leading fuel cell company. It is modeled as a compound growth option, and an explanation is provided for the difference in valuation arrived at by using the dynamic discounting cash flow method.